2019
DOI: 10.3390/catal9050468
|View full text |Cite
|
Sign up to set email alerts
|

High Cell Density Conversion of Hydrolysed Waste Cooking Oil Fatty Acids Into Medium Chain Length Polyhydroxyalkanoate Using Pseudomonas putida KT2440

Abstract: Waste cooking oil (WCO) is a major pollutant, primarily managed through incineration. The high cell density bioprocess developed here allows for better use of this valuable resource since it allows the conversion of WCO into biodegradable polymer polyhydroxyalkanoate (PHA). WCO was chemically hydrolysed to give rise to a mixture of fatty acids identical to the fatty acid composition of waste cooking oil. A feed strategy was developed to delay the stationary phase, and therefore achieve higher final biomass and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 59 publications
0
20
0
Order By: Relevance
“…Kamilah and co-workers have also shown that wild type and engineered strains of C. necator were able to utilize WCO (palm oil) in the production of P(3HB) and P(3HB-co-3HHx), respectively (Kamilah et al, 2013(Kamilah et al, , 2018. In a separate study, it was reported that P. putida strain KT2440 was able to produce high contents of mcl-PHAs when grown via high cell density fermentation using hydrolyzed WCO as the sole carbon source (Ruiz et al, 2019). Kourmentza et al, on the other hand, have reported co-production of P(3HB) polymers along with rhamnolipids when Burkholderia thailandensis was employed for the bioconversion of used cooking oil.…”
Section: Biosynthesis Of Phas Using Waste Plant Oilsmentioning
confidence: 99%
“…Kamilah and co-workers have also shown that wild type and engineered strains of C. necator were able to utilize WCO (palm oil) in the production of P(3HB) and P(3HB-co-3HHx), respectively (Kamilah et al, 2013(Kamilah et al, , 2018. In a separate study, it was reported that P. putida strain KT2440 was able to produce high contents of mcl-PHAs when grown via high cell density fermentation using hydrolyzed WCO as the sole carbon source (Ruiz et al, 2019). Kourmentza et al, on the other hand, have reported co-production of P(3HB) polymers along with rhamnolipids when Burkholderia thailandensis was employed for the bioconversion of used cooking oil.…”
Section: Biosynthesis Of Phas Using Waste Plant Oilsmentioning
confidence: 99%
“…The reason behind this is a genetic makeup that leads to the metabolism of a specific carbon feed (Ashby and Foglia, 1998). Ruiz et al (2019) studied the effect of hydrolyzed waste cooking oil fatty acids (HWCOFA) that showed HWCOFA could be used as the sole substrate for PHA production by P. putida KT2440. Glucose was also a suitable substrate for PHA production (Mohapatra et al, 2015).…”
Section: Influence Of Physical Parameters On Pha Productionmentioning
confidence: 99%
“…The implemented feed strategy delayed the stationary phase to enhance biomass and PHA formation. Use of intermittent feeding and conditions that led to HCDC, P. putida KT2440 reached a total biomass, %-mcl-PHA content in the CDW and overall productivity of 159.4 g/L, 36.4% (i.e., 57 g/L mcl-PHA) and 1.93 g/L/h, respectively [ 250 ]. This bioprocess provides a strong foundation that, with further process optimization, could lead to a commercially viable process for conversion of WCO to PHA.…”
Section: Industrial/agro-industrial Waste For Production Of Scl-and Mcl-phamentioning
confidence: 99%